Correction: Spin-phonon coupling and high-temperature phase transition in multiferroic material YMnO3. Issue 4 (5th January 2016) - Gupta, Mayanak Kumar; Mittal, Ranjan; Zbiri, Mohamed; Sharma, Neetika; Rols, Stephane; Schober, Helmut; Chaplot, Samrath Lal
Abstract : Correction for 'Spin-phonon coupling and high-temperature phase transition in multiferroic material YMnO3 ' by Mayanak Kumar Gupta et al., J. Mater. Chem. C, 2015, 3, 11717–11728.